The characterization of 17β-hydroxysteroid dehydrogenase type 2 (17βHSD2) activity towards novel C19 substrates. - Barnard, Monique (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.